Kwentong bakwit a video documentary series on bakwit school to educate and encourage undergraduate students to volunteer, donate, and advocate for the Lumad people's cause - Paderes, Sofia A.
Since President Duterte's declaration of Martial Law in Mindanao in May 2017, the increased attacks Lumad schools have forcibly displaced Lumads, the non-Muslim indigenous Mindanawon groups, from their own communities. This resulted in their evacuation to Metro Manila and the establishment of Bakwit School. The Lumads are in Metro Manila not only to learn in a safe space but to educate the public on their plight and call them to action.